Does Fear of Isolation Disappear Online? Attention-Seeking Motivators in Online Political Engagement - Shim, KyuJin (2019)
This study investigated the effects of fear of isolation (FOI) on political content consumption and creation in the context of online communication. Using more than 1,000 respondents from South Korea, the study empirically tested a theoretical model of FOI on political content consumption and expressions with two mediators (i.e., attention/status-seeking, and anonymity-seeking). Results indicated that FOI is related to seeking attention and status in political outlets also connected to anonymity-preference that leads to political expression. Implications for political communication scholarship and for practitioners are that voters’ political participations can be understood in a framework different from traditional focus on persuasion, political ideology, or demographics because—in today’s virtual and interactive media environment—users are more content consumers or community participants.